Sharing Success: A Review of Strategic Planning, Annual Reports, and Publicly Available Information from Academic Libraries - Springmier, Kaitlin; Edwards, Elizabeth; Bass, Michelle B. (Evidence Based Library and Information Practice, 2018)
Objective – This paper reports on a study which explored web-based information sharing practices in North American academic libraries. This study specifically focused on how selected academic libraries use data, reports, and other strategic planning documents to communicate success and demonstrate impact to stakeholders, administrators, and peers.Methods – An environmental scan was conducted to explore the assessment programs and communication practices of 97 North American academic libraries. The population for this study was identified on the basis of several metrics: consortial membership, Association of Research Libraries (ARL) ranking on various criteria, and institutional attendance at the 2014 and 2016 Library Assessment Conferences (LAC). Researchers conducted content analyses on the websites of the 97 libraries to identify measures of institutional support for assessment and to explore the range, depth, and quality of data made available. These iterative analyses were supported by the use of a rubric developed based on emergent criteria observed during multiple phases of review.Results – Of the libraries reviewed, 57% made some form of data available to the public. The most robust and effective use of data observed in this study involved the use of data to tell stories about the library and its impact. While this study found a positive correlation between libraries with clear investments in assessment and their use of data in public documents, it found that other factors such as an institution’s consortial memberships or funding model may more strongly influence a library’s decision to make data available.Conclusions – While observations gleaned from this study may serve as a benchmark for evaluating communication practices in academic libraries, further research is necessary to understand how factors within an academic library, its parent institution, or the profession at large may contribute to this decision making process.